2010
DOI: 10.1542/peds.2010-1609
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Faces Scales for the Self-report of Pain Intensity in Children

Abstract: For clinical use, we found no grounds to switch from 1 faces scale to another when 1 of the scales is in use. For research use, the FPS-R has been recommended on the basis of utility and psychometric features. Data are sparse for children below the age of 5 years, and future research should focus on simplified measures, instructions, and anchors for these younger children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
337
1
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(388 citation statements)
references
References 199 publications
10
337
1
18
Order By: Relevance
“…Furthermore, the whisper test does not take into consideration the elderly person's perception of his/her own hearing loss, or any loss of functionality, nor the social, family and psychological impact. This means the subjective faces scale may be an important complementary tool for functional screening of hearing loss, given its psychometric characteristics (area under the ROC curve = 0.81), and the fact that it is simple and easy to apply, having been originally developed for a population that has problem communicating -pediatric patients 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the whisper test does not take into consideration the elderly person's perception of his/her own hearing loss, or any loss of functionality, nor the social, family and psychological impact. This means the subjective faces scale may be an important complementary tool for functional screening of hearing loss, given its psychometric characteristics (area under the ROC curve = 0.81), and the fact that it is simple and easy to apply, having been originally developed for a population that has problem communicating -pediatric patients 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…The subjective faces scale became a common tool to measure pain in the 80s, in particular among pediatric patients due to its simplicity and ease of use 13,14 . Normally this scale uses five to seven stylized faces, each one a circle with unchanging eyes and a mouth that changes from a smile -an almost half-circle turned up, meaning happiness or extreme satisfaction, through a similar half-circle turned down, meaning sadness or extreme dissatisfaction 15 .…”
Section: Introductionmentioning
confidence: 99%
“…27,[29][30][31]36 Authors of these reviews suggest further research is needed for applicability of findings to meet the needs of children with cognitive impairments and physical disabilities. 35,92 Against these reviews, we sought to address this gap by systematically reviewing and critiquing pediatric assessment tools to be used to evaluate chronic pain interference in children with CP across a broad range of physical and developmental function.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Although previous reviews have identified measures to inform clinical practice, the application to children with disabilities is lacking. [27][28][29][30][31]35,36 Therefore, the primary aim of this review was to identify, describe, and critique pediatric chronic pain assessment tools currently available and make recommendations for clinical use for children with CP. To address the gap between research and practice, a secondary aim was to select relevant assessment tools for inclusion in a clinical practice toolbox to support health care professionals in their efforts to accurately identify and assess chronic pain in children with physical disabilities.…”
mentioning
confidence: 99%
“…Faces pain scales include the Faces Pain Scale (FPS), Faces Pain Scale-Revised (FPS-R), Oucher Pain Scale, and Wong-Baker Faces Pain Scale (WBFPS). Tomlinson compared these four measurements and found that children preferred the WBFPS [3]. Salivary alpha-amylase (SAA) concentrations have been used to determine pain-induced stress levels.…”
Section: Introductionmentioning
confidence: 99%